OPTIMIZATION OF MUSTARD PLANT (Brassica juncea L.) GROWTH THROUGH THE APPLICATION OF VARIOUS CONCENTRATIONS OF COLCHICINE IN A HYDROPONIC SYSTEM - indriani, indriani; AR, Trisnawaty; Syarifuddin, Rifni Nikmat; Mubarak, Husnul (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Mustard greens (Brassica juncea L.) are one of the vegetables widely consumed by the Indonesian population because they are low in calories but full of micronutrients such as vitamins A, C, and K, and essential minerals like calcium and manganese, making the demand for this plant very high. However, this substantial demand has not been matched by relatively low production by farmers. This is because mustard greens are generally grown naturally using small-scale land cultivation systems. As a result, efforts to increase plant production through Colchicine, which is used in polyploidy induction to produce plants with multiple chromosomes, have been applied. The large cell size resulting from polyploidy is expected to provide better growth and yield. The application of a hydroponic system in mustard green cultivation allows the plants to absorb nutrients and colchicine compounds optimally, making their utilization more effective and efficient in plant growth. This research aims to determine the appropriate colchicine concentration on the number of chromosomes, growth, and yield of mustard greens. The study was arranged in a Randomized Block Design (RBD) with colchicine concentration treatments consisting of six levels: 0% concentration as control, 1% colchicine, 2% colchicine, 3% colchicine, 4% colchicine, and 5% colchicine, each treatment repeated four times to obtain 24 observation units. The results showed that the application of colchicine at a 5% concentration had the best effect on growth and production, especially in parameters of plant height, number of leaves, and fresh weight.